Prevalence and Causes of Low Vision in Urban vs. Rural Populations (Medicine Today, 2025)
Introduction: Low vision is a significant global public health issue, affecting millions and leading to reduced quality of life. In developing countries like Bangladesh, low vision is often due to uncorrected refractive errors, cataracts, and other preventable conditions. There are disparities in the prevalence and causes of low vision between urban and rural populations, driven by differences in healthcare access, socio-economic status, and awareness. Objective: To assess the prevalence, causes, and socio-economic impact of low vision in urban and rural populations in Bangladesh. Method and Materials: This cross-sectional comparative study was conducted at the Ophthalmology Department, Shaheed Tajuddin Ahmed Medical College, Gazipur, over two years (January 2021–December 2022). A total of 124 participants were included using stratified random sampling. Comprehensive eye exams and demographic data were collected. The study used descriptive statistics and chi-square tests for analysis, with a p-value of